2020
DOI: 10.4103/jfmpc.jfmpc_1200_19
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neuroticism and suicidal thoughts among medical students: Moderating role of attachment styles

Abstract: Aim: The present study strives to find an experimental response to these questions: “Is the relationship between neuroticism and suicidal thoughts a simple relationship? Or are there other psychopathological variables such as attachment styles that also affect it?” Subjects and Methods: In this cross-sectional study, 376 medical students were selected from the three major cities of Iran using multi-stage sampling method from July 2018 to September 2018 and were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
2
16
4
3
Order By: Relevance
“…ings as they reported 17% of Iranian medical students. 20 Although there is a need for further studies, it seems that the learning environment and universities are not major contributing factors for suicidal ideation among Iranian medical students. Mohammadinia ideation among nursing, midwifery, and medical emergency students of Zahedan University of medical sciences.…”
Section: Figure 1 Association Between Suicidal Ideation and Hopelessnessmentioning
confidence: 99%
See 2 more Smart Citations
“…ings as they reported 17% of Iranian medical students. 20 Although there is a need for further studies, it seems that the learning environment and universities are not major contributing factors for suicidal ideation among Iranian medical students. Mohammadinia ideation among nursing, midwifery, and medical emergency students of Zahedan University of medical sciences.…”
Section: Figure 1 Association Between Suicidal Ideation and Hopelessnessmentioning
confidence: 99%
“…19 In a study on medical students of Zahedan University of Medical Sciences, 17% of medical students had suicidal ideation, which is relatively high. 20 Also, 7.2% of medical students had high-risk suicidal ideation, which is concerning. 20 To summarize, the suicidal rate is higher among medical students and physicians compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecure attachment may increase the impact of stressful life events on individuals, leading to the emergence of pathological psychology [ 23 ]. A study involving medical students showed that attachment style can be used as a variable to regulate suicidal thoughts [ 24 ] and insecure attachment linked to increased risk of suicide [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One important factor, related to suicidal ideation, is childhood history of abuse and maltreatment [16,[27][28][29][30]. This factor is fundamentally associated with borderline personality disorder (BPD) in older age [31].…”
Section: Introductionmentioning
confidence: 99%